Uma análise do filme “Agripina é Roma-Manhattan”, de Hélio Oiticica - Santos, Paloma da Silva (2020)
This study analyzes the movie Agripina é Roma-Manhattan(1972), based on the concept of “nonnarration” elaborated and exercised by the artist Hélio Oiticica and the considerations about the narration in the modern cinema anchored in the Deleuzian thought. With this, this aims intends to finally verify how the nonnarration and the narrativity of the post-war cinema are conected. For this investigation were carried out documentary research and bibliographic research, as well as film analysis. Thus, this work turns to a segment of Oiticica’s work still little explored and makes it possible to glimpse as salutary questions the poetics of the artist was incorporated to his reflection and cinematographic practice and how that dialogue with a portion of the cinematography of that time.